Cuticular hydrocarbons for identifying Sarcophagidae (Diptera) - Moore, Hannah E.; Hall, Martin J. R.; Drijfhout, Falko P.; Cody, Robert B.; Whitmore, Daniel (Nature Publishing Group, 2021)
The composition and quantity of insect cuticular hydrocarbons (CHCs) can be species-specific as well as sexually dimorphic within species. CHC analysis has been previously used for identification and ageing purposes for several insect orders including true flies (Diptera). Here, we analysed the CHC chemical profiles of adult males and females of eleven species of flesh flies belonging to the genus Sarcophaga Meigen (Sarcophagidae), namely Sarcophaga africa (Wiedemann), S. agnata Rondani, S. argyrostoma Robineau-Desvoidy, S. carnaria (Linnaeus), S. crassipalpis Macquart, S. melanura Meigen, S. pumila Meigen, S. teretirostris Pandellé, S. subvicina Rohdendorf, S. vagans Meigen and S. variegata (Scopoli). Cuticular hydrocarbons extracted from pinned specimens from the collections of the Natural History Museum, London using a customised extraction technique were analysed using Gas Chromatography–Mass Spectrometry. Time of preservation prior to extraction ranged between a few weeks to over one hundred years. CHC profiles (1) allowed reliable identification of a large majority of specimens, (2) differed between males and females of the same species, (3) reliably associated males and females of the same species, provided sufficient replicates (up to 10) of each sex were analysed, and (4) identified specimens preserved for up to over one hundred years prior to extraction.